The Western Region of Costa Rica in historical perspective. Palmares from the 19th century - Rodríguez Sancho, Javier (2021)
The article focuses on interpreting a series of border, ecclesiastical, municipal and district conflicts that occurred in the Western Region of Costa Rica between the 19th and 20th centuries. In addition, it exposes the agricultural changes between the subsistence of the poor peasants and the subsequent commercialization, however, the main focus is around the canton of Palmares. At the same time, it shows, the economic changes that took place in the 20th century.